2015
DOI: 10.1590/2317-1545v37n1135472
|View full text |Cite
|
Sign up to set email alerts
|

Physiological changes in osmo and hydroprimed cucumber seeds germinated in biosaline water

Abstract: ABSTRACT-Biosaline agriculture has been a viable alternative for agricultural production in regions with lack of good quality water. To enable the cultivation of vegetables in high electrical conductivities, seed priming has been used to increase tolerance to stress caused by use of brackish water. We aimed to evaluate the efficiency of osmo and hydropriming in cucumber seeds cv. Caipira germinated biosaline in water, regarding germination and biochemical changes during the germinative process. The experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 15 publications
(10 reference statements)
3
13
0
Order By: Relevance
“…Similar to the results in this study, a reduction in osmotic potential of the substrate caused by NaCl solution impaired seed germination and development of seedlings in other cucurbits such as watermelon (TORRES, 2007;SILVA et al, 2015), melon (ARAGÃO et al, 2009;SECCO, 2010), and cucumber (MATIAS et al, 2015). Average germination time (AGT), average germination speed (AGS) and germination speed index (GSI) all indicate the speed of germination of seeds and showed similar results ( Figure 2).…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…Similar to the results in this study, a reduction in osmotic potential of the substrate caused by NaCl solution impaired seed germination and development of seedlings in other cucurbits such as watermelon (TORRES, 2007;SILVA et al, 2015), melon (ARAGÃO et al, 2009;SECCO, 2010), and cucumber (MATIAS et al, 2015). Average germination time (AGT), average germination speed (AGS) and germination speed index (GSI) all indicate the speed of germination of seeds and showed similar results ( Figure 2).…”
Section: Resultssupporting
confidence: 84%
“…The presence of ions such as sodium and/or potassium may destabilise the osmotic balance and/or membranes and metabolic processes involved in repair of cell structures (YANG et al, 2008), leading to a drastic reduction of growth and accumulation of dry matter with increasing electrical conductivity, such as those observed in the present work and in other cucurbits (MATIAS et al, 2015;DANTAS et al, 2015). Thus, plant survival depends on the ability to adapt to stress, which acts as a selective pressure, and the factors acting on the tolerance to high salinity levels are frequently dependent on the physiological complexity of the plant (ARZANI, 2008).…”
Section: Resultssupporting
confidence: 51%
See 1 more Smart Citation
“…These crops are only harmed by EC levels higher than 11 dS m -1 (Torres, 2007;Secco et al, 2010, Matias et al, 2015b. In addition, the use of BSW with EC of approximately 4.0 dS m -1 did not affect the germination of cucumber seeds (Matias et al, 2015a).…”
Section: Resultsmentioning
confidence: 97%
“…The reason for this may be due to the stimulatory effect of sodium chloride, which has the effect of stimulating out of root in seed and increases the germination percentage at low concentration of salt. Matias et al (2015) reported seed priming more efficient to improve the performance of cucumber seedling in bio-saline water.…”
Section: Discussionmentioning
confidence: 99%